Exploration of Batik QR Code using Atumics Method to Increase the Functional Value of Batik - M. Amaruddin Yusuf; Emmareta Fauziah; Agatha Dinarah Sri Rumestri (ULTIMART Jurnal Komunikasi Visual, 2026)
Batik is an Indonesian ancestral heritage in the form of oral and intangible culture that has long been recognized by UNESCO. As time progresses, batik usage has diminished, particularly among the youth who prioritize practical, efficient technology such as QR Codes through the adoption of digitalization and QRIS. On the other side, the limitations of fashion MSMEs in providing information regarding alternative products brought to exhibitions have resulted in buyers not finding products that match their desires, so MSMEs need a product catalog to represent products that cannot be brought to exhibitions. This research attempts to combine batik and QR Codes using the atumics method to create a new product that is relevant to the times. By combining culture and technology, the batik QR Code can be filled with digital information links, one of which can be a digital catalog of fashion MSME products fostered by Rumah BUMN Pekalongan. It is hoped that with this research, batik will have a functional value that is harmonious with its aesthetic value and can provide an additional product alternative for buyers at exhibitions.